Theory Of Didactical Situation (TDS), Kajian Karakteristik dan Penerapannya dalam Pembelajaran Matematika - Nyiayu Fahriza Fuadiah (Jurnal Pendidikan Matematika:Judika Education, 2021)
This study aims to describe the characteristics of the Theory of Didactical Situation (TDS), especially in mathematics as an alternative information for educators to design learning according to the characteristics and needs of students and the learning objectives to be achieved. This study uses a literature review to explain the characteristics of TSD obtained from scientific papers and articles, relevant books, research reports, and other scientific sources. Based on the literature review, there are three characteristics of TDS, namely TDS' special attention to mathematics and its epistemology, epistemological characteristics, and students' cognitive dimensions. These three things are interrelated and support each other. This article also discusses the concept of adaptation through understanding adidactical situations and milieu and acculturation through understanding didactic situations and didactic contracts. In conclusion, through didactic situations that are built during learning and facilitated by the teacher, it is expected to be able to develop the potential of students, namely students can build their own knowledge to be achieved. Keywords: Theory of Didactical Situation, epistemological barriers, milieu, didactic contract, didactic situation